Interview Guide Development for Qualitative Research on Exploring Acceptance of Autonomous Vehicles in Thailand - Sithanant, Thana; Chaiyasoonthorn, Wornchanok; Chaveesuk, Singha (My University, 2023)
The aim of this article is to create a semi-structured interview guide for a qualitative research project centered on the exploring acceptance of autonomous vehicles (AVs) in Thailand. The widespread acceptance of AVs holds significant potential for enhancing the quality of life. While existing studies have predominantly focused on the acceptance of AVs through quantitative research and technology acceptance theories, this paper seeks to address this gap by proposing an innovative approach. This approach involves qualitative research rooted in the use of grounded theory methodology, employing semi-structured interviews to generate a novel theoretical framework. The collection of qualitative data will be facilitated through the adoption of semi-structured interviews, with the interview guide serving as the principal tool for data collection. The article will commence with a concise overview of AVs, pertinent technology acceptance theories, past research on AV acceptance, and the adoption of conventional car studies. Following that, a synthesis of knowledge and identification of gaps will be presented. Subsequently, a new research approach will be introduced, and a systematic procedure for crafting the semi-structured interview guide will be detailed and summarized.
Keywords: acceptance; autonomous vehicle; interview guide; qualitative research